Revisión estratigráfica de la Formación Ponón Trehué (Ordovícico), Bloque de San Rafael, Mendoza - Heredia, Susana Emma (2006)
This paper provides new descriptions and interpretations of the Ordovician rocks cropping out to the south of the Arroyo de Ponón Trehué, in the San Rafael Block, Mendoza Province. These data allow a new stratigraphic interpretation for the Ordovician rocks which leads to a formal redefinition of the Ponón Trehué Formation. These rocks are mainly siliciclastics (Darriwilian to lower Upper Ordovician), and two members are defined. The lower one is a siliciclastic/ carbonate sequence from the upper Middle Ordovician (upper Darriwilian) to the lower Upper Ordovician and the upper one is an olistostrome deposits that is correlated with the lower Upper Ordovician. The stratigraphic succession is interpreted in terms of the following geologic history: 1) Early to early Mid Ordovician: deposition on shallow marine carbonate platform. 2) Mid Ordovician (pre-P. serra zone): exposure and erosion of basement as result of a gentle uplift, which is thought to be a local, but not a regional, event because it is not recorded in other parts of the San Rafael Block nor in the Precordillera. 3) Mid to early Late Ordovician (P. serra to P. anserinus Zones): gentle subsidence and extensive flooding surface, and siliciclastic deposition in gradually deepening marine environment. 4) Early Late Ordovician: rapid increase in rate of deepening (basin subsidence) to create steep basin margin and collapse of carbonate blocks into basin. In order to create accommodation space for the thick olistostrome sequence including large olistoliths and to create steep basin margin necessary to generate gravity slide process, basin subsidence must have been rapid and tectonically driven.